FLORISTICS RELATIONS AND PHYTOSOCIOLOGY OF A SECONDARY MONTANE ARAUCARIA FOREST FRAGMENT IN LAGES, SANTA CATARINA STATE - Silva, Ana Carolina da (2012)
http://dx.doi.org/10.5902/198050985091This study investigated the floristic composition and the tree community structure in a secondary Araucaria Forest fragment in the Southern Plateau Region of Santa Catarina state, Brazil, the floristic context of this fragment in relation to other areas of Araucaria Forest in the region and the influence of climatic and geographic variables on the clustering patterns observed. The phytosociological of tree vegetation were assessed through 25, 400 m2, plots, where all trees with DBH (diameter at breast height) ≥ 5 cm were measured and identified.The floristic relationship among remnants and the influence of climatic and geographic variables were analized through a Multivariate Regression Tree, using a presence-absence species matrix and a climatic-geographic variables matrix. In the study area, 87 species were found, distributed into 36 botanic families. The species with the highest importance value were Araucaria angustifolia (Bertol.) Kuntze and Podocarpus lambertii Klotzsch. While the distribution of individuals in diametric classes was similar to an inverted J shape for the community, the populations demonstrated different shapes of diametric distribution. In the region, three floristic clusters were discriminated, influenced mainly by temperature seasonality and annual mean temperature. The study site was grouped with together with other areas presenting temperature seasonality higher or equal to 3.053oC.